Perfil epidemiológico e clínico de crianças e adolescentes com condições neurológicas de um ambulatório de fisioterapia pediátrica de uma universidade do interior do Amazonas - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2025)
Objective: to describe the epidemiological and clinical profile of children and adolescents with neurological conditions at a physiotherapy outpatient clinic at a university in the interior of Amazonas. Methods: this is a descriptive, retrospective cross-sectional study based on medical records. The study included children and adolescents aged between zero and 18 years who were assessed by the pediatric physiotherapy department at the Institute of Health and Biotechnology (ISB) in 2022 and the first half of 2023. Patients with missing data, outside the established period and records of the same patient from later evaluations were excluded. There were 11 losses and 33 patients made up the final sample. The data was subjected to descriptive analysis using Jamovi software, version 1.6.23.0. Results: the majority of the children were male, 22 (66.7%), with the largest age group being between 0 and 4 years old, 15 (45.5%). The most frequent health conditions were Cerebral Palsy alone 9 (278.3%) and with other conditions 8 (24.2%), followed by Autistic Spectrum Disorder 4 (12.1%). In the prenatal period, 8 (24.2%) had an infection and 8 (24.2%) of the mothers had an inadequate number of prenatal consultations; and in relation to perinatal factors, 9 (27.3%) were born preterm and 17 (51.5%) had a normal delivery. Conclusions: prenatal and perinatal characteristics were identified that are risk factors for the congenital neurological conditions found in these children and adolescents. The results of the research indicate a need for local investigation of the risk factors for acquiring these conditions, for more effective alignment between prenatal and perinatal health services, and to guide the implementation of specialized services for the care of these conditions.
Keywords: Perfil epidemiológico; Perfil de saúde; Crianças; Adolescentes; Fisioterapia; CIENCIAS DA SAUDE: FISIOTERAPIA E TERAPIA OCUPACIONAL; .; .